Trapped in representations : the silenced animal in J. M. Coetzee’s works - Eng, Charlene Gwendolene (2017)
For centuries, our conceptions of moral and legal obligations towards nonhuman animals have been in constant conflict. The moral consideration of animals was never a direct, unhindered march of progress from some prior historical moment to the early nineteenth century when the first legislation for the protection of animals was passed. Instead, the fight for animal rights proved itself to be fraught with difficulty, as it struggled with disagreements and has been bedeviled by the deep-seated attitude that animal subjugation is justified by the human acquisition of language, and the corollary ability to reason and form abstract concepts, in which animals are deemed impotent. Today, our knowledge of nonhuman animals have become increasingly profound and illuminated as we learn more about animal cognition and their behaviors in their natural environments. Dr. Jane Goodall launched her groundbreaking research with wild chimpanzees, and this meant that animal interests could no longer be ignored when at odds with our anthropocentric concerns, leading us to scientifically reconsider the ways in which human and animal lives are intertwined.